2020
DOI: 10.1094/mpmi-12-19-0341-r
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis Response Regulator 6 (ARR6) Modulates Plant Cell-Wall Composition and Disease Resistance

Abstract: The cytokinin signaling pathway, which is mediated by Arabidopsis response regulator (ARR) proteins, has been involved in the modulation of some disease-resistance responses. Here, we describe novel functions of ARR6 in the control of plant disease-resistance and cell-wall composition. Plants impaired in ARR6 function (arr6) were more resistant and susceptible, respectively, to the necrotrophic fungus Plectosphaerella cucumerina and to the vascular bacterium Ralstonia solanacearum, whereas Arabidopsis plants t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 107 publications
5
56
0
Order By: Relevance
“…1A). These data support the diverse and significant functions of cell walls on plant disease resistance responses to vascular and necrotrophic pathogens, as previously described (20,29,54). Our data also identified an unanticipated contribution of cell walls to plant resistance to biotrophic oomycetes, like H. arabidopsidis (Fig.…”
Section: Disease Resistance Responses Of Cell Wall Mutants Issupporting
confidence: 91%
See 4 more Smart Citations
“…1A). These data support the diverse and significant functions of cell walls on plant disease resistance responses to vascular and necrotrophic pathogens, as previously described (20,29,54). Our data also identified an unanticipated contribution of cell walls to plant resistance to biotrophic oomycetes, like H. arabidopsidis (Fig.…”
Section: Disease Resistance Responses Of Cell Wall Mutants Issupporting
confidence: 91%
“…Similar immune responses triggered by elicitor activities have been described in wall extracts of additional Arabidopsis wall mutants (12,44). We found that the PEC1 and PEC2 wall extracts from cwm plants, and particularly PEC1 from at1g23170-1, acs8-2, namt1-1, arr6-3 and irx10-1, triggered early immune responses, like Ca +2 bursts, upon their application to Arabidopsis pMAQ lines expressing the apoaequorin Ca +2 sensor protein (20,47; SI Appendix, Fig. S12).…”
Section: Disease Resistance Responses Of Cell Wall Mutants Issupporting
confidence: 78%
See 3 more Smart Citations